PROGRAM HOLISTIK E-LEARNING DI PERGURUAN TINGGI ISLAM - Kusumaputri, Erika (Universitas Ahmad Dahlan, 2011)
The purpose of this study was to identify the Critical Success FactorsModel for implementing e-learning in the Islamic university and to proposestrategies derived from the perspective of holistic, consultative, andemancipatory. Analysis of CSF was trying to uphold the organization usingresearch methods to identify the purpose of management as essentialelements that were important in achieving the effectiveness of the changeprocess. Data were analyzed from depth interviews and focused groupdiscussion with university leaders, chief of Puskom, and quality assuranceunit, referred to the number of CSF, which were grouped into 4 groups,namely: leadership, structural and cultural design, technology, and deliveryof content. The result of this study shows that every element of highereducation institutions is prepared to be able to attach them to e-learningin supporting the development of career or profession. So, we need theability of universities to manage the change process through discussionswith the proposed design objectives (goal).